Influence Of Employee's Spiritual Motivation On Employee Performance (Empirical Study In Santri Works Of Taarid Tauhid Bandung Foundation) - Iman Aryadi; Laili Rahmawati (Universitas Pendidikan Indonesia, 2019)
The development of foundations and businesses led by Abdullah Gymnastiar. The question arises as to why this business that is labeled with the heart of management is such a way of developing (not only becoming one of the business centers; it also becomes a